2007
DOI: 10.1111/j.1440-1843.2007.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost of hospitalizing asthma patients in a regional hospital in Thailand

Abstract: Cost of hospitalizing asthma patients in a regional hospital in Thailand CHUESAKOOLVANICH K. Respirology 2007; 12: [433][434][435][436][437][438] Background and objective: The hospitalization of asthma patients accounts for substantial costs in any health-care system. However, the utilization of medical resources and the cost of hospitalizing asthma patients in Thailand have never been evaluated. This study aimed to evaluate the utilization of health-care resources and itemize the cost of hospitalizing asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 24 publications
4
33
1
Order By: Relevance
“…This figure is similar to the 81%, 84%, and 89% found in Turkey, Germany, and Australia, respectively [10,16,22], but higher than other studies which reported that medication costs corresponded to a range between 30 and 47% direct costs of asthma care [12][13][14]. The differences in prescription costs noted may be due to differences in the types of medication given to the patients, doses of medication required by each patient, and the severity of their asthma.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This figure is similar to the 81%, 84%, and 89% found in Turkey, Germany, and Australia, respectively [10,16,22], but higher than other studies which reported that medication costs corresponded to a range between 30 and 47% direct costs of asthma care [12][13][14]. The differences in prescription costs noted may be due to differences in the types of medication given to the patients, doses of medication required by each patient, and the severity of their asthma.…”
Section: Discussionsupporting
confidence: 64%
“…The differences in prescription costs noted may be due to differences in the types of medication given to the patients, doses of medication required by each patient, and the severity of their asthma. Furthermore, lower cost of laboratory tests and consultations in developing countries compared with developed countries might have accounted for the lower treatment costs observed in our setting [8][9][10][11][12][13][14]. Also, we have shown that costs of follow-up care for asthma patients did not differ significantly across age, education, marital status, residence, or gender categories.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations